Estrous synchronization and fertility in allyl trenbolone-treated gilts - Jeffrey S Stevenson; W E Schmidt; Duane L Davis (Kansas Agricultural Experiment Station Research Reports, 1981)
Onset of estrus in gilts fed allyl-trenbolone for either 14 or 18 days was controlled effectively. The stage of the cycle at the beginning of treatment had little effect on the synchronization response. More than 97% of the treated gilts showed estrus within 3 to 8 days after the last progestagen feeding. Treatment did not affect gestation length, farrowing rate, or litter size.; Swine Day, Manhattan, KS, November 12, 1981
Keywords: Swine day; 1981; Kansas Agricultural Experiment Station contribution; no. 82-128-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 406; Swine; Synchronization; Fertility; Allyl-trenbolone; Gilts